Sub-decadal variations in outlet glacier terminus positions in Victoria Land, Oates Land and George V Land, East Antarctica (1972–2013). Issue 5 (26th April 2017) - Lovell, A.M.; Stokes, C.R.; Jamieson, S.S.R.
Abstract: Recent work has highlighted the sensitivity of marine-terminating glaciers to decadal-scale changes in the ocean–climate system in parts of East Antarctica. However, compared to Greenland, West Antarctica and the Antarctic Peninsula, little is known about recent glacier change and potential cause(s), with several regions yet to be studied in detail. In this paper, we map the terminus positions of 135 glaciers along the coastline of Victoria Land, Oates Land and George V Land from 1972–2013 at a higher temporal resolution (sub-decadal intervals) than in previous research. These three regions span a range of climatic and oceanic conditions and contain a variety of glacier types. Overall, from 1972–2013, 36% of glaciers advanced, 25% retreated and the remainder showed no discernible change. On sub-decadal timescales, there were no clear trends in glacier terminus position change. However, marine-terminating glaciers experienced larger terminus position changes compared with terrestrial glaciers, and those with an unconstrained floating tongue exhibited the largest variations. We conclude that, unlike in Greenland, West Antarctica and the Antarctic Peninsula, there is no clear glacier retreat in the study area and that most of the variations are more closely linked to glacier size and terminus type.